Проект словника обрядових фразеологізмів східнослобожанських говірок - Царьова, І. (Лексикографічний бюлетень, 2011)
The article deals with ethnic and cultural features of the semantics of ritual phraseologisms
of easternslobozhshanskiy dialect. Actuality of research is due to the necessity
to create ritual phraseological dictionary, focuses on search patterns of synchronic ethnographic
nominations and traced slices. The foundamental base is lexical author ritual
contexts, numbering about 750 items, collected and arranged field method, the registry
phrasebook eastern slobozhshanskiy and eastern- velds dialects of Donbass by V. Uzhchenko
and D. Uzhchenko (2005), large volume (1008 p.). work “Life and Creativity
of pagans of Kharkiv province: Essays on ethnography of the region” edited by V. Ivanov
(1898). The proposed research focused on solving one of the most fundamental issues of
linguistics is phraseological derivation in ethno cultural space of East Slobozhanshchina.
Proves that the formation of semantic values of ritual phraseologicals are involving all
aspects of its importance, the priority of which is denotative aspect.